Validación del sistema de purificación de agua de la empresa Tecmol farmacéutica S.A.S (2017)
A prospective validation was developed at Tecmol Farmacéutica SAS, in which three grades were performed: operational qualification, in this qualification it was verified through documentation that the system behaves as expected in all preset operating ranges and works properly within Of the limits of its operating conditions. The design qualification (DQ) consisted of a preliminary study to ensure that the implementation of the design was feasible within the company. After the design approval was approved, the installation qualification (IQ) was verified by means of a documented review and verified that all important aspects of the installation were in conformity with the design specifications and with the manufacturer's recommendations. In order to provide a comprehensive report, statistical tools were used to provide accurate and accurate data. The parameters to be evaluated were the index of capacity, linearity and repeatability, and with respect to the operating conditions the use of the pharmacopoeia USP 34-NF was used, which served as a guide to stipulate the limits that under normativity are allowed in type I water And type II.